A nation rising : Hawaiian movements for life, land, and sovereignty - Goodyear-Kaʻōpua, Noelani; Hussey, Ikaika; Wright, Erin Kahunawaikaʻala, 1973- (Narrating native histories., 2014)
A Nation Rising chronicles the political struggles and grassroots initiatives collectively known as the Hawaiian sovereignty movement, raising issues that resonate far beyond the Hawaiian archipelago, issues such as Indigenous cultural revitalization, environmental justice, and demilitarization.